2019
DOI: 10.1021/acsami.8b21276
|View full text |Cite
|
Sign up to set email alerts
|

Designing Structural-Color Patterns Composed of Colloidal Arrays

Abstract: Structural coloration provides a great potential for various applications due to unique optical properties distinguished from conventional pigment colors. Structural colors are nonfading, iridescent, and tunable, which is difficult to achieve with pigments. In addition, structural color is potentially less toxic than pigments. However, it is challenging to develop structural colors because elaborate nanostructures are a prerequisite for the coloration. Furthermore, it is highly suggested the nanostructures be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 194 publications
0
86
0
Order By: Relevance
“…[32][33][34][35][36] Moreover, the periodic pore structure of the inverse opal particles generated brilliant structural colors which enabled sensing and self-reporting of the adsorption state, as manifested by the reflection peak shift of the MIPIOPs. [37][38][39][40][41] It was demonstrated that the hierarchically structured MIPIOPs, integrated with the herringbone mixer, realized efficient cleaning of multiple targets both in water and in serum. Therefore, this novel platform offers great potential in clinical blood purification and artificial kidney construction.…”
Section: Doi: 101002/adma202005394mentioning
confidence: 99%
“…[32][33][34][35][36] Moreover, the periodic pore structure of the inverse opal particles generated brilliant structural colors which enabled sensing and self-reporting of the adsorption state, as manifested by the reflection peak shift of the MIPIOPs. [37][38][39][40][41] It was demonstrated that the hierarchically structured MIPIOPs, integrated with the herringbone mixer, realized efficient cleaning of multiple targets both in water and in serum. Therefore, this novel platform offers great potential in clinical blood purification and artificial kidney construction.…”
Section: Doi: 101002/adma202005394mentioning
confidence: 99%
“…As is well known, the long-range order structures of the colloidal crystals result in their iridescent characteristic and angle dependence. [36][37][38] Therefore, once the long-range order has been transformed into a short-range order and the arrangement of nanoparticles becomes an amorphous state, a non-iridescent and angle-independent material will be obtained. 19,20 The amorphous feature of our pigments was verified through the SEM images and their corresponding 2D Fourier analysis, as shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…As the resonant wavelength for the diffraction is determined by the interparticle distance and refractive index, various colors can be developed using a single set of materials, unlike chemical pigments. [ 1–10 ] More importantly, the structural color can be dynamically tuned by changing the interparticle distance or refractive index in real time. For example, interparticle separation can be controlled by applying an electric field on suspensions of charged colloidal particles or composites of colloidal particles or cavities in the matrix of electroresponsive polymers, resulting in structural‐color change.…”
Section: Introductionmentioning
confidence: 99%